2013
DOI: 10.1038/hr.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antihypertensive medication adherence on hospitalization for cardiovascular disease and mortality in hypertensive patients

Abstract: Antihypertensive medication treatment is one effective management strategy to prevent cardiovascular disease (CVD) and mortality. However, little research has been conducted on the rates of antihypertensive medication adherence and the effect of antihypertensive medication adherence on health outcomes in South Korea. We searched the Korean National Health Insurance Claims Database for records from 2003 to 2007. Patients in this study were 18 years of age or older and they were diagnosed with hypertension and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
91
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 39 publications
7
91
2
2
Order By: Relevance
“…Our study provides further support for previous findings 12,13,31 about the association of adherence to antihypertensive medication on hospitalization for CVD. Compared with those patients with good medication adherence, patients with poor adherence were 1.42× more likely to require hospitalization for AMI.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Our study provides further support for previous findings 12,13,31 about the association of adherence to antihypertensive medication on hospitalization for CVD. Compared with those patients with good medication adherence, patients with poor adherence were 1.42× more likely to require hospitalization for AMI.…”
Section: Discussionsupporting
confidence: 81%
“…32,33 Whereas many previous findings were restricted to patients with diabetes mellitus or with previous CVD, [34][35][36] few studies have reported the importance of hypertensive medication adherence in primary prevention. Most research into primary prevention found a relationship between adherence to antihypertensive medication and CVD events 12,31,32 or all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations